Spontaneous bacterial peritonitis – therapeutic challenges in the era of increasing drug resistance of bacteria - Rostkowska, Karolina; Szymanek-Pasternak, Anna; Simon, Krzysztof (Clinical and Experimental Hepatology, 2018)
Spontaneous bacterial peritonitis (SBP) is one of the most common bacterial infections in patients with liver cirrhosis and it significantly contributes to the deterioration of the prognosis and increased risk of mortality. Previous data suggested that the most common pathogens causing SBP are G-negative aerobic bacteria and treatment recommended by the international guidelines (EASL, AASLD) is highly effective. In recent years, due to the widespread use of antibiotic prophylaxis and the increased frequency of hospitalization along with the use of invasive procedures in patients with cirrhosis, the involvement of Gram-positive cocci and multi-drug resistant bacteria in the etiology of SBP is increasing. This is related to the lowering of the effectiveness of the first-line therapy used so far and worsening of the prognosis, increasing in-hospital mortality. In this work we summarize current data on the characteristics of pathogens responsible for SBP in the context of currently recommended treatment regimens.